Influence of age on static postural control in adults with type 2 diabetes mellitus: a cross-sectional study - Zhuang, Yujun; Hong, Zhenzhen; Wu, Lijuan; Zou, Chunyan; Zheng, Yan; Chen, Liming; Yin, Lianhua; Qin, Jiawei (Frontiers in Endocrinology, 2023)
Aim It was the aim of this study to assess static postural control characteristics in people with type 2 diabetes mellitus (T2D) of different ages using a force platform. A relationship was also established between static postural control parameters and age in this study. Methods A total of 706 participants with T2D were included in this study. The participants were stratified into three age groups: Group 1 (<60 years old), Group 2 (60–70 years old), and Group 3 (>70 years old). Static postural control assessment during two-leg stance was performed on a force platform by all participants. The center of pressure (CoP)-related parameters were measured under two stance conditions (eyes open and closed). Kruskal–Wallis tests were applied to explore the difference among the different age groups. Multivariate regression analysis was performed to determine the relation between age and static postural control parameters. Results Group 1 (<60 years old) had significantly less CoP total tracking length (TTL), sway area (SA), and CoP velocity along the Y direction (V-Y) under both eyes-open and eyes-closed conditions compared with Group 2 (60–70 years old) and Group 3 (>70 years old). Group 1 (<60 years old) had significantly less CoP maximum sway length along the X direction (MSL_X) and longer tracking length each area unit (TTL/SA) under the eyes-open condition compared with Group 2 (60–70 years old) and Group 3 (>70 years old). There was a significantly positive correlation between age and the most static postural parameters such as CoP TTL, SA, MSL-X, MSL-Y, and V-Y. There was a significantly negative correlation between age and TTL/SA. Conclusion This study suggested that older T2D participants had worse static postural control ability than younger ones. Most static postural parameters presented a significant correlation with age; the higher the age, the worse the static postural control.